Come, let us eat together : sacraments and Christian unity - Wheaton Theology Conference (2017 : Wheaton College, Ill.); Kalantzis, George (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2018)
As Christians, we are called to seek the unity of the one body of Christ. But when it comes to the sacraments, the church has often been -- and remains -- divided. What are we to do? Can we still gather together at the same table? Based on the lectures from the 2017 Wheaton Theology Conference, this volume brings together the reflections of Protestant, Roman Catholic, and Eastern Orthodox theologians, who jointly consider what it means to proclaim the unity of the body of Christ in light of the sacraments. Without avoiding or downplaying the genuine theological and sacramental differences that exist between Christian traditions, what emerges is a thoughtful consideration of what it means to live with the difficult, elusive command to be one as the Father and the Son are one.
The supper of the Lord : goodness and grace in 1 Corinthians 11:17-34 / Amy Peeler -- Churches and the politics of the sacraments : rethinking "unity of the church" / D. Zac Niringiye -- In persona Christi : the Catholic understanding of the ordained priesthood in relation to the eucharist / Thomas G. Weinandy, OFM, Cap. -- A way forward : a Catholic-Anabaptist ecclesiology / D. Stephen Long -- Ascension, communion, and the hospitality of the priest-king / Cherith Fee Nordling -- The gospel we share and the unity we seek : Orthodox eucharistic ecclesiology / Bradley Nassif -- Christ the Ursakrament / Katherine Sonderegger -- Visual ecumenism : the coy communion of art / Matthew J. Milliner -- The eucharist, the risen Lord, and the road to Emmaus : a road to deeper unity? / Matthew Levering -- The eschatological dimension of sacramental unity : an Orthodox Christian view / Paul L. Gavrilyuk -- "For you have been planted together with Christ" : sacraments and the life of the church / George Kalantzis -- Who invited the Baptist? : the "sacraments" and free church theology / Marc Cortez -- Sacraments and (dis- )unity : a constructive ecumenical proposal toward healing the divisions and facilitating mutual recognition
Includes bibliographical reference and index.
Originally presented at Wheaton Theology Conference in 2017.
Keywords: Sacraments and Christian union -- Congresses; Lord's Supper and Christian union -- Congresses; Conference papers and proceedings